1998
DOI: 10.1007/s002510050396
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of rat CD1 typifies evolutionarily conserved CD1D class genes

Abstract: The non-major histocompatibility complex (MHC)-encoded CD1 family has recently emerged as a new antigen-presenting system that is distinct from either MHC class I or class II molecules. In the present study, we determined the genomic structure of the rat CD1 locus. It was extremely similar to mouse CD1 genes, especially to CD1D1. The 5' flanking region of the CD1 gene contained the binding motifs for two cytokine-inducible transcription factors, NF-IL2-A and NF-IL6. Some regulatory elements found in MHC class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The rat also expresses genes for CD1d (22,23) and the AV14, AJ18 (6), and BV8S2 (24) gene segments, which are highly similar to those of the mouse (Ͼ80% sequence similarity of the translated products). Peculiar to the rat is the existence of a multimember AV14 gene family and the organ-specific preferences of certain AV14AJ18 rearrangements.…”
Section: T He Hallmark Of Invariant Nkt Cells (Inkt Cells)mentioning
confidence: 99%
See 1 more Smart Citation
“…The rat also expresses genes for CD1d (22,23) and the AV14, AJ18 (6), and BV8S2 (24) gene segments, which are highly similar to those of the mouse (Ͼ80% sequence similarity of the translated products). Peculiar to the rat is the existence of a multimember AV14 gene family and the organ-specific preferences of certain AV14AJ18 rearrangements.…”
Section: T He Hallmark Of Invariant Nkt Cells (Inkt Cells)mentioning
confidence: 99%
“…PCR product was cloned into TOPO cloning vector and sequenced. The sequence was identical with rat CD1d (GenBank accession number AB029486) published by Katabami et al (23). Mouse and rat CD1d DNA were cloned into EcoRI site of pczCGZ5IZ and pczCGZ5 IEGZ vectors, respectively, and were further used for retroviral infection of P80rCD80 cells.…”
Section: Cloning and Expression Of Rat And Mouse Cd1dmentioning
confidence: 99%
“…Two classes of CD1 genes have been identified (13,14). Whereas the classic CD1 genes were absent in rats and mice, CD1D gene has been conserved through mammalian evolution including mice, rats, rabbits, sheep, and humans (14 -19).…”
mentioning
confidence: 99%
“…On the contrary, Brossay et al reported that murine CD1d was mainly expressed on hemopoietic cells but not by the epithelium of the digestive tracts (24). Therefore, from a phylogenetic standpoint, several investigators have hypothesized that CD1d molecules have a similar functional significance in various mammalian immune systems (1,13,18,25). To elucidate the immunological significance of NKT cells and their interaction with CD1d, especially in a variety of unique disease models established in rats, it is very important to obtain information about the rat invariant TCR ␣-chain.…”
mentioning
confidence: 99%
“…Rats have a CD1d gene whose expression pattern on hematopoietic cells is nearly identical to that of mouse CD1d, different BV8S2 homologues (BV8S2 and BV8S4), and generate typical AV14/AJ18 rearrangements [15,[18][19][20][21]. A direct identification of rat iNKT cells has been possible only recently by staining of primary rat iNKT cells with rat CD1d dimers [22].…”
Section: Introductionmentioning
confidence: 99%